SOSIALISASI AKTIVITAS PROGRAM STUDI FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN ALAM (FMIPA) GUNA MENINGKATKAN MINAT SISWA TERHADAP ILMU MIPA DI SEKOLAH MENENGAH ATAS NEGERI 6 PALANGKA RAYA - Luqman Hakim; Jhon Wesly Manik; Vinsen Willy Wardana; Lilis Rosmaniar; Yohanes Edy Gunawan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Many students of grade XII of SMAN 6 Palangka Raya do not know much about the study program at the Faculty of Mathematics and Natural Sciences (FMIPA) of Palangka Raya University. The Faculty of Mathematics and Natural Sciences is committed to providing as much information as possible to prospective students regarding study programs, facilities, activities, academic and non-academic excellence and alumni. The socialization activity of the study program activities of the Faculty of Mathematics and Natural Sciences (FMIPA) to increase student interest in science at Palangka Raya State Senior High School 6 was carried out by presenting material about FMIPA, Palangka Raya University, program activities, studies, products/applications of science, as well as achievements and alumni. The delivery of information on the FMIPA Study Program is useful for increasing student interest in science at Palangka Raya State Senior High School 6. It is hoped that it will attract students' interest in continuing their studies at FMIPA, Palangka Raya University.